Novel tetrakis 4-(hydroxymethyl)-2,6-dimethoxyphenoxyl substituted metallophthalocyanines: Synthesis, electrochemical redox, electrocatalytic oxygen reducing, and volatile organic compounds sensing and adsorption properties - Gunay, Ipek; Orman, Efe Baturhan; Altindal, Ahmet; Salih, Bekir; Ozer, Metin; Ozkaya, Ali Riza (ELSEVIER SCI LTD, 2018)
Novel tetrakis [(4-(hydroxymethyl)-2,6-dimethoxyphenoxyl)] substituted zinc(II), cobalt(II) and iron(II) phthalocyanines were synthesized by the reaction of (4-(hydroxymethyl)-2,6-dimethoxyphenoxy)phthalonitrile with suitable metal salts in 2-N, N-dimethylaminoethanol. The phthalonitrile ligand was prepared from 4-hydroxy-3,5-dimethoxy benzyl alcohol and 4-nitrophthalonitrile using potassium carbonate as catalyst in N,N-dimethylformamide at 50 degrees C. The structural characterization of the compounds was carried out by elemental analysis, FTIR, UV-vis and MALDI-TOF Mass spectroscopic methods. Electron transfer properties and electrocatalytic oxygen reducing performances of the compounds were also investigated by electrochemical, in situ spectroelectrochemical and in situ electrocolorimetric measurements. Electrochemical, in situ spectroelectrochemical, and in situ electrocolorimetric measurements showed that rich redox behavior of the complexes leads to their high electrocatalytic activity for oxygen reduction and net electrocolorimetric changes suitable for electrochromic applications. Phthalocyanine central metal ion effect on the sensing properties and the adsorption kinetics of four main groups of volatile organic compounds (alkanes, alcohols, chlorinated hydrocarbons and amines) onto these novel compounds were also examined by three different models. While the sensitivity of the sensors was strongly dependent on the nature of the metal ion, no considerable effect was observed on the adsorption kinetics. The evaluation of the kinetics of adsorption processes with respect to three different models showed that pseudo second order rate equation best describes the adsorption of alcohols and chlorinated hydrocarbons while the adsorption of alkanes and amines on these compounds can be represented by Elovich equation.
Keywords: Phthalocyanine; Electrochemistry; In situ spectroelectrochemistry; Oxygen electrocatalysis; VOC sensing; VOC adsorption; HETERO-DINUCLEAR PHTHALOCYANINES; IN-SITU SPECTROELECTROCHEMISTRY; DECKER LU(III) PHTHALOCYANINES; BALL-TYPE PHTHALOCYANINES; METAL-FREE; THIN-FILMS; ELECTRICAL-PROPERTIES; COBALT PHTHALOCYANINES; REDUCTION REACTION; BEARING COUMARIN; Chemistry; Engineering; Materials Science